1997
DOI: 10.1097/00006534-199702000-00043
|View full text |Cite
|
Sign up to set email alerts
|

A Reversed-Flow Latissimus Dorsi Musculocutaneous Flap Based on the Serratus Branch in Primary Shoulder Reconstruction

Abstract: We report a case using the latissimus dorsi musculocutaneous flap based on the serratus branch in primary shoulder reconstruction. The reversed flow of the serratus branch maintained the circulation of the flap following acute disruption of the thoracodorsal vessels. Although our case was unusual, the reversed-flow latissimus dorsi flap based on its serratus branch may add a useful option in some cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 5 publications
0
8
0
1
Order By: Relevance
“…Cauldfied et al 10 reported successful salvage of a thrombosed DIEP flap by performing a retrograde anastamosis with the distal serratus branch of the thoracodorsal vessel and it has also been described in the salvage of latissimus dorsi pedicled flaps. 13,14 Our group reported retrograde arterial and venous drainage in a double pedicle DIEP flap 15 and has recently studied the retrograde limb of the IMV and determined it to be a viable option as a recipient vein in DIEP breast reconstruction. 16,17 Our cases discuss the use of retrograde anastamoses for flap salvage in breast reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Cauldfied et al 10 reported successful salvage of a thrombosed DIEP flap by performing a retrograde anastamosis with the distal serratus branch of the thoracodorsal vessel and it has also been described in the salvage of latissimus dorsi pedicled flaps. 13,14 Our group reported retrograde arterial and venous drainage in a double pedicle DIEP flap 15 and has recently studied the retrograde limb of the IMV and determined it to be a viable option as a recipient vein in DIEP breast reconstruction. 16,17 Our cases discuss the use of retrograde anastamoses for flap salvage in breast reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…23 The delay phenomenon may not even be necessary, as groups have reported a reversed blood flow of the serratus branch after acute ligation of the thoracodorsal vessels. 13,14,29 Shigehara et al 29 reported a specific case where the muscle, based on its serratus branch, was used for shoulder reconstruction after resection of an osteosarcoma in a 19-year-old woman. The thoracodorsal vessels had been resected with the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the teres major muscle can also be divided to help swing the flap into the defect. 14,29 If there is concern regarding the flap's viability after division of the circumflex scapular pedicle or the teres major muscle is to be preserved, the flap can be supercharged by reanastomosing the circumflex scapular anterior to the teres major. 31 On the basis of these reports and our experience, if we were to encounter a situation after claviculectomy in which the thoracodorsal vessels were compromised, we would still proceed with a latissimus dorsi muscle flap, given its bulk and proven durability.…”
Section: Discussionmentioning
confidence: 99%
“…It has a reliable vascular supply and can be easily transferred to cover anterior shoulder defects. 8,17 However, the latissimus dorsi can usefully be utilized to reconstruct irreparable rotator cuff tears 1 and was, therefore, preserved in the cases described for possible cuff reconstruction at a later date.…”
Section: Discussionmentioning
confidence: 99%